Can Stakeholder Collaboration Model being used for controlling the land use change of Rice Fields in Bone Regency, South Sulawesi Province? - Armawadin, Armawadin (Jurnal Ilmiah Administrasi Publik, 2022)
This study examines the collaborative model of stakeholders controlling the conversion of paddy fields in Bone Regency, South Sulawesi Province. This study use descriptive qualitative method. Using the collaborative governance of Anshell and Gash, the study showed that the rapid paddy land use change can be minimized using the collaborative perspective. However, the collaboration must be performed in 3 aspect include paddy land map making, paddy preservation incentives and community empowerment. The paddy preservation land use policy can be enhanced using collaborative governance. The results of the study indicate that the collaboration of stakeholders in controlling the conversion of paddy fields can be carried out based on 3 (three) collaboration models, namely collaboration of maps making of protected paddy fields, collaboration in providing incentives and collaboration for community protection and empowerment.